Konsep Beauty Privilege Membentuk Kekerasan Simbolik - Shinta Aprilianty; Siti Komariah; Mirna Nur Alia Abdullah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This research was conducted starting from the majority of Twitter users who expressed their disquiet about beauty privilege or special treatment for someone who was considered "meeting beauty standards". Therefore, it is important to examine how the form of beauty privilege becomes a form of symbolic violence. This study uses a qualitative approach with phenomenological methods, and the data collection techniques used are in the form of observation, interviews, and documentation. The results of this study state that forms of beauty privilege occur based on several environments such as the educational environment, work environment, family environment, friendship environment, and community environment.